Rational exploitations: economic criteria & indicators for sustainable management of tropical forests - Ruitenbeek, J.; Cartier, J. (Center for International Forestry Research, 1998)
If one is of the mindset that the world is fundamentally chaotic and irrational, then the discpline of economics probably has little to offer. But if one accepts the notion that there is some method to the apparent madness of individuals, governments and organizations, then economic inquiry does have no some contributions to make. In this excercise, we argue that economic criteria and indicators of sustainable forest management should reflect the dimensions of efficiency, equity and sustainability, and need to look beyond the forest stand to institutional and policy issues. If we let such criteria inform our decisions, we may yet end up with exploitation of the forests. It would, however, be rational exploitation; rational explotation reflecting an enlightened self-interest that captures the broader global needs of current and future generations